Kombinasi Pupuk NPK dan Monosodium Glutamat (MSG) untuk Tanaman Pakcoy (Brassica rapa chinensis L.) Varietas Nauli F1 - Simarmata, Albert Raja; Azizah, Elia; Subardja, Vera Oktavia (UNIVERSITAS LABUHANBATU, 2023)
Pakcoy (Brassica rapa chinensis L.) is a vegetable plant that is widely used in Indonesian dishes for consumption. One important factor that supports success in the production of pakcoy plants is the fertilization process. The purpose of this study was to obtain the best-combined dose of NPK and Monosodium Glutamate (MSG) compound fertilizer on the growth and yield of pakcoy plants. The research was carried out in February and March 2023 using polybags in Cigelam, Muktijaya Village, Setu District, Bekasi Regency, West Java Province. The research used an experimental method with an environmental design, namely a single factor Randomized Block Design (RBD) consisting of 5 treatments, namely A (1.2 g NPK control), B (1.2 g NPK and 6 g MSG), C (1.2 g NPK and 9 g MSG), D (1.2 g NPK and 12 g MSG), and E (1.2 g NPK and 15 g MSG). Each treatment was repeated 5 times so that 25 experimental units were obtained. Observations of the data obtained were analyzed using the F test analysis with a level of 5% and further tested DMRT level of 5%. The experimental results showed that there was a significant effect on the height of the pakcoy plants at 28 HST and 35 HST, the number of leaves at 28 HST and 35 HST, and the leaf area of the pakcoy plants. The combination of NPK and MSG fertilizer in treatment B (1.2 g NPK and 6 g MSG) gave the highest results in observing plant height at 28 HST and 35 HST, number of leaves at 28 HSTand 35 HST, leaf area.Â Keywords: Monosodium Glutamate, NPK, Pakcoy